Preparation of human amniotic membrane for transplantation in different application areas - Hofmann, Nicola; Rennekampff, Hans-Oliver; Salz, Anna Katharina; Börgel, Martin (Frontiers in Transplantation, 2023)
The human amniotic membrane (hAM) is the inner layer of the placenta and plays protective and nutritional roles for the fetus during pregnancy. It contains multiple growth factors and proteins that mediate unique regenerative properties and enhance wound healing in tissue regeneration. Due to these characteristics hAM has been successfully utilized in ophthalmology for many decades. This material has also found application in a variety of additional therapeutic areas. Particularly noteworthy are the extraordinary effects in the healing of chronic wounds and in the treatment of burns. But hAM has also been used successfully in gynecology, oral medicine, and plastic surgery and as a scaffold for in vitro cell culture approaches. This review aims to summarize the different graft preparation, preservation and storage techniques that are used and to present advantages and disadvantages of these methods. It shows the characteristics of the hAM according to the processing and storage methods used. The paper provides an overview of the currently mainly used application areas and raise new application possibilities. In addition, further preparation types like extracts, homogenates, and the resulting treatment alternatives are described.